Interinstitutional collaboration with military dictatorship: The case concerning judicial censorship on the National Truth Commission (Revista Direitos Humanos e Democracia, 2025)
The military dictatorship that started in Brazil in march 1964 has consequences experienced even today, highlighting that only in 2014 the works of the National Truth Commission (NTC), department belatedly created in the country to inquiry for the truth and guarantee the memory of the authoritarian regime. It happens that NTC has been targeted in a delegitimating process which aims to deny the military dictatorship, integrating the central aspect of this research the study of a judicial decision that ordered the name withdraw of a person responsible for crimes against humanity, as listed in the NTC’s Final Report. Though the methodology of case study, the paper aims to answer the following question: the effective protection of democracy is a consistent interpretative standard uses by the officials that acted in the case? In conclusion, it is demonstrated that a kind of interinstitutional authoritarian collaboration is discovered in the research, compromising the official protection of democracy in Brazil.
Keywords: Transitional justice; National Truth Commission; Interinstitutional authoritarian collaboration